can someone help me, please?
![can someone help me please class=](https://us-static.z-dn.net/files/df2/d67f948d3d0912cf88fe429476680f01.png)
![can someone help me please class=](https://us-static.z-dn.net/files/d4f/f8d46a0c8520ef905a92760dfea34f53.png)
![can someone help me please class=](https://us-static.z-dn.net/files/dd2/62ddf6db99c542e3705a71df9ed6cbe4.png)
from f(0) we find that
y = mx - 1
from f(-1) we find that the equation is
y = -3x - 1
1)
inverse f(x) :
x = -3y - 1
y = -(x + 1) / 3 x = -1
y = -(-1 + 1) / 3
y = 0
2)
y also equal to 0 since x = -1
3)
f^-1(2) = -(2+1) / 3
= -3/3
= -1
f(-1) = 2